Aspects of the twins's development - Μαρκοδημητράκη, Μαρία; Κουγουμουτζάκης, Γιάννης; Κοκκινάκη, Θεανώ (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF